Optimizing the Instagram Algorithm Through Digital Content Posting Strategies to Increase Customer Engagement: A Case Study on the Instagram Account @meneljahitanku_ - Dwi Citra Chairani; Haryadi Haryadi (Economic: Journal Economic and Business, 2025)
This study aims to analyze, develop, and evaluate the effectiveness of digital content posting strategies tailored to the Instagram algorithm to increase customer engagement on the @meneljahitanku_ account. The background of this study is the difficulty of MSMEs in understanding the complex mechanisms of the Instagram algorithm, resulting in stagnant customer interaction despite a sufficient number of followers. Using a qualitative single case study approach, data was collected through semi-structured interviews (before & after intervention), observations, and content experiments for 30 days (July–August 2025). The results showed significant improvements: the engagement rate increased from 1.62% to 6.74%; impressions increased by 384.20% (from 25,500 to 123,471); followers increased by 5.67%. The Reels format and the Testimonial content pillar proved to be the most effective in triggering engagement.